PEMASYARAKATAN PROFETIK : TINJAUAN POLITIK PROFETIK TERHADAP UNDANG-UNDANG NOMOR 22 TAHUN 2022 - Royyan Mahmuda Al'Arisyi Daulay (An Natiq, 2023)
Law Number 22 of 2022 concerning Corrections is a new policy by the State in implementing the national prison system. However, in the process of legislation, this policy has experienced a lot of rejection due to the bad image that is often heard by the public. Even though this policy contains values ​​that live in society, religion and Pancasila. This study aims to explore social values ​​with a prophetic political review. Prophetic political theory has 3 elements, namely humanization, liberation and transcendence. This research method is a qualitative research of literature with a normative-juridical approach using descriptive-analytic techniques. Primary data is Law Number 22 of 2022 and secondary data is literature on prophetic politics. These data were collected and then analyzed and described comprehensively. As a result, according to the prophetic political view, the concept of correctional institutions in Law Number 22 of 2022 contains the values ​​of humanization, liberation and transcendence in its principles and articles. Studies on correctional institutions need to be increased in order to add to the body of knowledge regarding the prison system and increase public Knowles about the positive values ​​of correctional facilities. The discussion of prophetic values ​​in Law Number 22 of 2022 is reflected in principles such as the principle of protection, equality of treatment and service, respect for human dignity and worth, loss of independence is the only suffering, and the guarantee of the right to keep in touch with family and other people certain people. So that it can be said that Law no. 22 of 2022 concerning Corrections as a policy that has prophetic political values.